Enhanced biomass production and nutrient removal capacity of duckweed via two-step cultivation process with a plant growth-promoting bacterium, Acinetobacter calcoaceticus P23. (January 2020) - Ishizawa, Hidehiro; Ogata, Yuka; Hachiya, Yoshiyuki; Tokura, Ko-ichiro; Kuroda, Masashi; Inoue, Daisuke; Toyama, Tadashi; Tanaka, Yasuhiro; Mori, Kazuhiro; Morikawa, Masaaki; Ike, Michihiko
Abstract: Plant growth-promoting bacteria (PGPB) are considered a promising tool to improve biomass production and water remediation by the aquatic plant, duckweed; however, no effective methodology is available to utilize PGPB in large hydroponic systems. In this study, we proposed a two-step cultivation process, which comprised of a "colonization step" and a "mass cultivation step, " and examined its efficacy in both bucket-scale and flask-scale cultivation experiments. We showed that in the outdoor bucket-scale experiments using three kinds of environmental water, plants cultured through the two-step cultivation method with the PGPB strain, Acinetobacter calcoaceticus P23, yielded 1.9 to 2.3 times more biomass than the control (without PGPB inoculation). The greater nitrogen and phosphorus removals compared to control were also attained, indicating that this strategy is useful for accelerating nutrient removal by duckweed. Flask-scale experiments using non-sterile pond water revealed that inoculation of strain P23 altered duckweed surface microbial community structures, and the beneficial effects of the inoculated strain P23 could last for 5–10 d. The loss of the duckweed growth-promoting effect was noticeable when the colonization of strain P23 decreased in the plant. These observations suggest that the stable colonization of the plant with PGPB is the key for maintaining the accelerated duckweed growth and nutrient removal in this cultivation method. Overall, our results suggest the possibility of an improved duckweed production using a two-step cultivation process with PGPB. Highlights: A new duckweed cultivation process which enables effective PGPB use was proposed. The process reduces PGPB dose by separating colonization and cultivation steps. Remarkable improvements in duckweed growth and nutrient removal were attained. The growth-promotion by PGPB lasted for 5–10 days after the colonization step. Persistence of PGPB would be the key to maintain high performance of this process.